An Analysis of Taboo Language in “Harry Potter” Move By Jk Rowling - Riski Rahmayanti; Meristika Moetia (Syntax Idea)
Language has an important role in society, because language is a means for humans to communicate with each other, through language speakers can identify themselves as they understand their own language as a symbol. The language human use has meaning, meaning plays a very important role in all fields and helps in the understanding of Language. The researcher conducted this research to find out what types of taboo language are in the Harry Potter movie and to find out what type of taboo language most often used in the Harry Potter films. This research is descriptive qualitative research, data collection techniques by watching it repeatedly, then the researcher transcribes all the taboo words contained in the Harry Potter movie, then the researcher groups the taboo words according to Steven Pinker (2017). There are 4 types of taboo language namely: profanity, sexual language, regious taboo, and taboo word in socity. There are 9 taboo language in the Harry Potter movie. From the results above, the use of taboo words in the Harry Potter movie not only reflects the nature of the characters but also expresses feelings of anger, surprise and annoyance which aims to create character depth and a more realistic atmosphere.